Controversial Ideas about the State and Revolution, A Book Review “The State And Revolution” Vladimir Ilyich Lenin, Haymarket Books Chicago, 2014, 210 Pages, ISBN: 978-1-60846-498-2 (Journal of Indonesian Legal Studies, 2022)
The State and Revolution is a book that was born from Lenin's life experience as the father of Russian revolutionaries. The movement that gave birth to major changes in the future of Russia and the formation of a Soviet state with Marxism-Leninism. In his book, Vladimir Lenin divides the discussion into six chapters, each of which is divided into several sub-chapters. The method of writing the book uses a descriptive analysis pattern with a contextual approach. In fact, this book has a positive contribution to anti-bourgeois supporters, because of its ideas against bourgeoisie and Western capitalism. But this book is a negative ghost, for lovers of freedom and democracy. Because the true teachings of Leninism require authoritarianism and the absence of freedom for its citizens.